(untitled) (Bangladesh Journal of Nuclear Medicine, 2018)
Background: With the advancement of science, the scope of thyroid uptake in diagnosis and treatment of thyroid diseases has become limited. Uptake test with 99mTc pertechnetate along with a thyroid scan, which is done almost routinely, could be a better option when needed. This will not only exempt the patients from relatively higher radiation burden but also cause significant reduction of procedural time. Moreover, the thyroid image we get along with the uptake may guide with additional information. This study was done to provide preliminary data regarding thyroid uptake test with 99mTc in our population and to assess the possibilities of introducing this safer and convenient radionuclide in our routine practice. Patients and methods: This cross sectional, comparative study was conducted from January to December of 2015 on 59 participants in Institute of Nuclear Medicine and Allied Sciences, Dhaka. Patients coming for a radioactive iodine uptake test along with a thyroid scan were enrolled. Uptake of 99mTc pertechnetate at 20 minutes and at 24 hours was measured. Data were analyzed between the two uptake values based on clinical conditions, serum TSH levels and gland size. Results: Almost perfect agreement and a strong positive correlation (Kappa value=0.933 & r =0.845) were found between the results of two modalities. The hyperthyroid group showed a moderate agreement (k=0.5) and a moderate positive correlation (r=0.6). The participants with thyroiditis revealed a perfect agreement (k=1) and a strong positive correlation (r=0.981). Almost perfect correlation was found between participants with enlarged and non-enlarged glands (r=0.776 & 0.801 respectively). Agreement analysis revealed almost perfect agreement (k=0.88) in the group with enlarged and moderate agreement (k=0.6) in participants with non-enlarged glands. Low serum TSH group showed perfect agreement (k=1.0) and a strong positive correlation (r=0.748). The group with normal TSH level revealed a perfect agreement with k=1 but a moderate correlation (r=0.418). Conclusion: Good agreement and correlation were found between thyroid uptakes of 99mTc at 20 minutes by gamma camera and that of at 24 hours. Agreement and correlation in different clinical settings also showed consistency. So, 99mTc may be considered for uptake test in a regular basis in the limited fields where an uptake is still required as it may yield a reliable result in a simple, quicker and more convenient method. Bangladesh J. Nuclear Med. 20(2): 105-109, July 2017